Inhibitors of Acetylcholinesterase Derived from 7-Methoxytacrine and Their Effects on the Choline Transporter CHT1 - Kristofikova, Zdenka; Ricny, Jan; Soukup, Ondrej; Korabecny, Jan; Nepovimova, Eugenie; Kuca, Kamil; Ripova, Daniela (Dementia and geriatric cognitive disorders, 2017)
BACKGROUND: Reversible acetylcholinesterase inhibitors are used in Alzheimer disease therapy. However, tacrine and its derivatives have severe side effects. Derivatives of the tacrine analogue 7-methoxytacrine (MEOTA) are less toxic. METHODS: We evaluated new derivatives of 7-MEOTA (2 homodimers linked by 2 C4-C5 chains and 5 N-alkylated C4-C8 side chain derivatives) in vitro, using the rat hippocampal choline transporter CHT1. RESULTS: Some derivatives were effective inhibitors of rat acetylcholinesterase and comparable with 7-MEOTA. All derivatives were able to inhibit CHT1, probably via quaternary ammonium, and this interaction could be involved in the enhancement of their detrimental side effects and/or in the attenuation of their promising effects. Under conditions of disrupted lipid rafts, the unfavorable effects of some derivatives were weakened. Only tacrine was probably able to stereospecifically interact with the naturally occurring amyloid-β isoform and to simultaneously stimulate CHT1. Some derivatives, when coincubated with amyloid β, did not influence CHT1. All derivatives also increased the fluidity of the cortical membranes. CONCLUSION: The N-alkylated derivative of 7-MEOTA bearing from C4 side chains appears to be the most promising compound and should be evaluated in future in vivo research.
Keywords: alkylace; Quaternary Ammonium Compounds; synaptozomy; Rats; cholinesterasové inhibitory; Stereoisomerism; kvartérní amoniové sloučeniny; Alkylation; hipokampus; takrin; Tacrine; Cation Transport Proteins; mužské pohlaví; Cholinesterase Inhibitors; Choline; Rats, Wistar; Cholesterol; krysa rodu Rattus; amyloidní beta-protein; stereoizomerie; mozková kůra; Membrane Fluidity; Synaptosomes; zvířata; fluidita membrány; membránové mikrodomény; Cerebral Cortex; Membrane Microdomains; cholin; proteiny přenášející kationty; potkani Wistar; Hippocampus; Amyloid beta-Peptides; Male; cholesterol; Animals